Characteristics of freeze-dried nanoencapsulated fish oil with whey protein concentrate and gum arabic as wall materials - VAHIDMOGHADAM,Farideh (2019)
Abstract Fish oil has many health effects, but due to its strong odor and rapid spoilage, its use in food formulations is limited. For these reasons, nanoencapsulation of fish oil can be important. The purpose of this study was to investigate the influence of whey protein concentrate (WPC) and gum arabic as wall materials on the characteristics of nanoencapsulated fish oil powder. Gum arabic and WPC were used in varying amounts for nanoencapsulation of fish oil. An oil-in-water emulsion with 6% fish oil and 20% aqueous solution of wall materials was prepared by sonication (24 kHz for 120 sec). The diameter of the emulsion droplets was measured by particle size analysis and they then were dried in a freeze-drier. The results showed that the type and concentration of wall material influenced the characteristics of the nanocapsules. The smallest emulsion droplet diameter (50 nm) and the highest encapsulation efficiency were found in the sample containing 100% gum arabic; however, the lowest amount of surface oil, pH and highest zeta potential and moisture content also were recorded for this sample. It can be concluded that gum arabic is more suitable for nanoencapsulation and could appropriately contain the volatile compounds within the capsules.